Lollo rosa lettuce – a promising raw material for a new drugs development - Hrubnyk, M. I.; Davtian, L. L. (Тернопільський національний медичний університет імені І. Я. Горбачевського, 2023)
The aim of the work. Development of solid and semisolod dosage form with Lollo Rossa Lettuce extract with anti-inflammatory and antioxidant activity.
Keywords: lettuce; healing properties; gastrointestinal tract; nervous system; inflammatory processes; infectious diseases; phenolic acids; flavones; anthocyanins; Lollo Rossa Lettuce